E-Book Interaktif Berbasis Canva Sebagai Inovasi Sumber Belajar Materi Sistem Pencernaan Manusia Kelas V SD - Wahyu Ciptaningtyas; Bagus Amirul Mukmin; Kharisma Eka Putri (Jurnal Pemikiran dan Pengembangan Sekolah Dasar (JP2SD), 2022)
This research was based on observations at SDN Mrican 2 Kediri, which showed a low level of student learning in studying human digestive system material. As much as 48.38% of students scored below the KKM. This problem is caused by the teaching materials that students learn being less interesting and cannot provide a clear picture of the process of how humans digest food. The analysis of student needs shows that there is still a lack of electronic reading books for elementary school students provided at SDN Mrican 2 Kediri. In addition, 98% of students prefer learning material with writing, images, sound, and 95% of students like animation-based video material. Based on the problem analysis and needs analysis, the researchers developed an interactive Canva-based e-book teaching material as an innovative learning resource for the human digestive system. The purpose of this research is to develop Canva-based interactive e-book teaching materials. This study uses the R&D method with the ADDIE Model. Canva-based interactive e-book products are validated by expert media, material, and language validators. The results of this study indicate that the validity of media experts is 92%, material experts 88.9%, and linguists 100%, so the average validation result is 93.6%. The practicality of the educator response questionnaire is 94.7%, and the student response questionnaire is 90%, so the average practicality result is 92.35%. The results of the effectiveness of the product were obtained from the experimental results, where the effect of interactive e-books on learning outcomes reached 88.46% of students who completed. So it can be concluded that Canva-based interactive e-books are valid, practical, effective, and feasible.